Elder Alert: Building a Business Model for Home Healthcare - Meyer, Mark H.; Kursh, Steven R. (Senate Hall, 2012)
The case study provides an opportunity for entrepreneurship students to address decision making regarding a business model while also learning about doing financial projections
Keywords: business model|innovation|entrepreneurship in healthcare